Pediatric Clinic, Clinical Centre Kragujevac, Kragujevac, Serbia - Simović, Aleksandra M.; Košutić, Jovan Lj.; Prijić, Sergej M.; Knežević, Jasmina B.; Vujić, Ana J.; Stojanović, Nadežda D. (Vojnosanitetski pregled, 2014)
Background/Aim. In recent years, the focus of interest of the scientific community is the application of heart markers as early indicators and prognostic parameters of perinatal asphyxia (PA). The aim of this study was to evaluate the significance of clinical application of heart markers in term newborns with perinatal asphyxia. Methods. During a 3-year period we analyzed 91 full-term newborns (55 with and 36 without perinatal asphyxia). In all the subjects within the first 24–48 h after birth, we simultaneously determined serum concentrations of cardiac troponin I, brain natriuretic peptide, MB fraction of creatine kinase (CK-MB) and C-reactive protein. Results. In the group of full-term neonates with PA significantly higher levels of cardiac troponinI (p = 0.000), CK-MB fraction (p = 0.000), brain natriuretic peptide (p = 0.003) and C-reactive protein (p = 0.017) were found, compared to the group of healthy full-term newborns. In merged group (n = 91) cardiac troponin I level correlated with the fifth minute Apgar score (r = -0.637, p = 0.000) and the serum lactate concentration in the first 12h after birth (r = 0.529, p = 0.000). Early increase in cardiac troponin I > 0.135 µg/L predicted the risk of death with the sensitivity of 84.6% and specificity of 85.9%, while the increase in CK-MB fraction, brain natriuretic peptide and  C-reactive protein did not have a predictive value with respect to a mortality outcome. Conclusion. Among the tested cardiac markers, cardiac troponin I is the most sensitive and the only reliable early predictor of mortality in full-term neonates with perinatal asphyxia.
Keywords: perinatology; asphyxia; biological markers; heart failure; troponin I; sensitivity and specificity